Algerian 3D Panel Systems: Improving Thermal Comfort and Energy Efficiency in a Range of Climates - Sifodil, Djamel; Boualla, Nabila; Mokhtari, Abderrahmane Medjdoub; Messaoudi, Mohamed; Ibka, Mohamed Sofiane (Brazilian Journal of Production Engineering, 2025)
This study evaluates thermal comfort and energy efficiency in residential buildings in Oran and Béchar, Algeria—regions with contrasting climates. Using TRNSYS dynamic simulation, it examines how three types of building envelopes affect temperature stability and energy demands for heating and cooling. Findings highlight that building envelope design and material choice significantly impacts energy efficiency. Advanced 3D panel technology demonstrated notable energy savings, reducing consumption by up to 29% compared to traditional materials, while also maintaining thermal comfort in both climates. The study further investigates the energy performance of 3D panels, double-brick walls, and insulated double walls, showing that 3D panel systems consistently lower energy consumption by reducing heating and cooling needs. These results underscore the value of climate-responsive designs and passive cooling strategies, positioning 3D panel technology as a promising solution for enhancing thermal comfort and reducing energy use in Algeria’s residential sector.